KONSTRUK PEMIKIRAN AL-GAZALI - Chairul Wahid Septialana; Irawan Irawan; Popi Puadah; Suhaeni . (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2021)
This study aims to enable the reader to know, understand, and moreover be able to implement the thoughts of al-Ghazali about the study of philosophical epistemology in the general sense of being used to refer to the various questions that arise and arise in the human mind about the difficulties encountered, and try to find answers and the right solution to believe. about understanding Philosophy, when calling it a name of science in the most general sense. And in the Islamic world there is also someone who developed this theory and his name is al-Farabi or Abu Nashr al-Farabi which says "there is nothing in the mini style that cannot be entered by philosophy". This study uses a qualitative approach to the type of literature. So that the data source comes from books, journals, and articles and other references such as studies to a lecturer who is proficient in his field. The research data were collected by documentation techniques and analyzed and then conclusions were drawn. From this research it can be seen that al-Ghazali's thought in philosophizing is very scientific because it can be studied in the fields of epistemology, ontology, and axiology.